HUBUNGAN ANTARA PERKEMBANGAN MOTORIK HALUS DENGAN KEMAMPUAN MEMORI JANGKA PENDEK DI YAYASAN PENDIDIKAN ISLAM TK CENDANA BATAM KOTA - Susanti, Rini; Rusdani, Rusdani (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
The purpose of education in Kindergarten is to develop the child's development. One of child development is the development of fine motor and memory / short-term memory capacity of the child. The development of fine motor is a smooth coordination that uses smooth muscles, while the ability of short-term memory is a memory capability lasting a few seconds or at most a few minutes. The expectations of parents and teachers with the fine motor skills of children who grow normally along with the ability of memory / short-term memory of children. The research was conducted at the Islamic Education Foundation of TK Cendana Batam city for being supported by the stimulation of fine motor development and short-term memory by the teachers at Tk. For the aim that children do not have fine motor background and poor short-term memory skills. This research method is analytic observasional with approach of cross sectional conducted at Islamic Education Foundation of TK Cendana Batam City on 2017. Population in this research is student at Islamic Education Foundation of TK Cendana Batam City onÂ  2017 which amounted 52 peoples, using technique of taking total sampling. The statistical test used is chi-square test using the degree of significance of 95% Â from 52 respondents, where 26 respondents with smooth motor development of children who are not in accordance with the development of childrend with classification of 12 respondents (46.2%) have short-term memory capacity of children less, and 14 respondents (53,8%) have ability of memory short-term good, while 26 respondents who have a smooth motor development in accordance with age of development with a classification of 26 respondents (100%) have good short-term memory ability of children. The results of statistical test with chi-square obtained value p value = 0.00 <0.05, then Ho is rejected and Ha accepted.There is a correlation between the Development of Smooth Motoric Children With Short Term Memory Capacity of Children In Islamic Education Foundation TK Cendana Batam City on 2017